1984
DOI: 10.1056/nejm198410253111702
|View full text |Cite
|
Sign up to set email alerts
|

Renal Revascularization in the Azotemic Hypertensive Patient Resistant to Therapy

Abstract: We undertook this study to assess the frequency of renovascular hypertension in patients with azotemia and hypertension refractory to drug therapy and to determine the effects of renal revascularization on blood pressure and renal function in these subjects. Thirty-nine of 106 consecutive patients admitted for diagnostic evaluation of severe hypertension proved to have renovascular hypertension. Of 21 hypertensive patients with renal insufficiency, 10 appeared to have renovascular hypertension with either bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(28 citation statements)
references
References 26 publications
2
25
0
1
Order By: Relevance
“…Furthermore, while medical therapy may control blood pressure, renal function often deteriorates nonetheless. 22 Numerous approaches to the diagnosis of renovascular hypertension have been advocated enthusiastically over the last 30 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while medical therapy may control blood pressure, renal function often deteriorates nonetheless. 22 Numerous approaches to the diagnosis of renovascular hypertension have been advocated enthusiastically over the last 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…37 The second is a well-described group of patients who also have normal blood pressures but exhibit renal insufficiency on the basis of progressive renal ischemia and may benefit from revascularization. 22 The diagnostic utUity of simplified captopril renography was not evaluated in patients of either of these first two classes.…”
mentioning
confidence: 99%
“…In our solitary kidney subgroup, 2 of 3 patients showed an improvement in their renal function. Encouraging results in the preservation of renal function have been reported by other centers (3,17,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 61%
“…In patients with bilateral stenoses, the beneficial effects of revascularization are present especially after bilateral repair (36), although the Cleveland group reported that their results were not very different from those in patients with unilateral revascularization of only the more stenotic artery (37). In bilateral disease, both kidneys, in fact, are relatively protected from the unfavourable effects of high systemic blood pressure (3). In this study, after bilateral PTRA, 1 of 6 patients improved and in 2 of 6 patients the renal function remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation